Integration of Religious Values and Papuan Local Wisdom in Education at Sorong Muhammadiyah University - Lestari Lestari; Muhammad Rusdi Rasyid; Indria Nur; A'mal Jadid (Jurnal Eduslamic, 2026)
This study investigates how Sorong Muhammadiyah University integrates Islamic values, theological reflection, and Papuan local wisdom into teaching, from Muslim and non‑Muslim stakeholder perspectives. A 40‑item Likert questionnaire (n=100: 50 Muslim, 50 non‑Muslim) and semi‑structured interviews with 10 students (5 Muslim, 5 non‑Muslim) and 4 lecturers (2 Muslim, 2 non‑Muslim) were used. Quantitative data were analyzed descriptively (means, percentages); qualitative data underwent open coding, categorization, and thematic synthesis. Findings indicate generally positive perceptions of religious and theological integration, while systematic incorporation of Papuan local wisdom and full inclusion of non‑Muslim perspectives received lower, though moderate, ratings. The paper proposes a context‑specific model of integrative religious education for Islamic higher education in Papua and offers recommendations for curriculum design, lecturer professional development, and institutional policy to promote more inclusive, locally rooted, and theologically informed practices.